PERBANDINGAN KONSENTRASI HARA DAUN KELAPA SAWIT (Elaeis guineensis Jacq.) USIA 6 DAN 8 TAHUN - Oksana Oksana; Hermansah Hermansah; Agustian Agustian; Syafrimen Yasin (Jurnal Agroteknologi, 2026)
Oil palm productivity is closely linked to the nutrient status of its leaves, which serve as a reliable indicator of plant health and fertilizer requirements. Comparing leaf nutrient levels at different ages, such as 6 and 8 years, provides valuable insights into the dynamics of nutrient uptake and the optimization of fertilization strategies for sustainable yield. This study was conducted to assessing the macronutrient adequacy status of oil palm leaves based on diagnostic standards, and knowing the differences in these nutrients at ages 6 and 8 years. Leaf samples were taken from Kampar District, Riau Province by systematic random sampling of 14 oil palm trees to represent 20 ha of each age class. Leaf samples are leaves located on the 17th leaf sheath in the oil palm leaf phyllotaxis system. Analysis of plant nutrient levels using the X-ray fluorescence (XRF) series PAnalitycal Epsilon 3 method except for N-total with Kjeldhal (% dry weight). Results revealed that 6-year-old oil palms had optimal amounts of N, K, Ca, and Mg, along with elevated P and S. Conversely, 8-year-old palms showed deficiencies in N, K, Mg, and S, but optimal level of Ca and high P levels. T-test analysis (P value < 0.05) indicated significant differences in N, K, and S between the two age groups, while P, Ca, and Mg did not differ significantly.